ITOCHU : a Japanese firm in the era of retrenchment and reform - Zhu, Ying, 1961-; Rowley, Chris, 1959-; Warner, Malcolm ([London] : SAGE, 2016)
ITOCHU is used here as an example of recent HR retention and training development. The company, which was founded in 1858 and grew over the years, changes the HR retention policies focusing on specialization instead of job rotation, in order to attract capable young people to join the organisation and promote long-term commitment.
Originally Published in: Harzing, A. W., & Pinnington, A. (2011). ITOCHU - A Japanese Firm in the Era of Retrenchment and Reform. In International human resource management (3rd ed., pp. 431-435). London: SAGE Publications Ltd. Print. ISBN: 9781847872937.
Description based on online resource; title from home page (viewed on April 21, 2016).
Keywords: elektronické knihy; electronic books; Ito Chu Shoji Kabushiki Kaisha; Personnel management -- Case studies